2007
DOI: 10.1139/h07-024
|View full text |Cite
|
Sign up to set email alerts
|

A lifestyle intervention of weight-gain restriction: diet and exercise in obese women with gestational diabetes mellitus

Abstract: This study assessed whether a weight-gain restriction regimen, with or without exercise, would impact glycemic control, pregnancy outcome, and total pregnancy weight gain in obese subjects with gestational diabetes mellitus (GDM). A total of 96 subjects with GDM met the inclusion criteria and were sequentially recruited, with 39 subjects self-enrolled in the exercise and diet (ED) group, and the remaining 57 subjects self-enrolled in the diet (D) group owing to contraindications or a lack of personal preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
158
0
18

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(187 citation statements)
references
References 19 publications
3
158
0
18
Order By: Relevance
“…Other intervention studies among overweight and obese pregnant women have also evaluated birthweight and gestational age at delivery as outcome variables (18,19,21). No differences were found between the intervention-and control groups, which are in line with our findings (12).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Other intervention studies among overweight and obese pregnant women have also evaluated birthweight and gestational age at delivery as outcome variables (18,19,21). No differences were found between the intervention-and control groups, which are in line with our findings (12).…”
Section: Discussionsupporting
confidence: 89%
“…In two earlier intervention studies on pregnant obese women no differences in the cesarean section rate could be detected (18,19). In our study population there were no differences between the groups in the rates of planned as well as acute cesarean sections and instrumental deliveries (12).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Increasing attention towards interventions that may be used to improve maternal health could, therefore, impact substantially on offspring health both in the short and long term. A number of early reviews, 19,[22][23][24][25] in addition to two recent studies, 26,27 have identified altering maternal carbohydrate intake as well as maternal physical activity levels as potential strategies for positively regulating maternal weight gain and offspring birth weight among other pregnancy outcomes. However, longitudinal studies that describe the potential long-term benefits of these interventions for offspring health are lacking.…”
Section: Maternal Obesity And/over-nutrition Predisposes Offspring Tomentioning
confidence: 99%
“…Given the importance of PA, the American College of Obstetrics and Gynecology, the Society of Obstetrics and Gynecology Canada/ Canadian Society for Exercise Physiology, and the International Olympic Committee have issued specific guidelines that encourage all pregnant women to engage in routine PA in the absence of contraindications [18][19][20]. Regular moderate intensity PA during pregnancy has consistently been shown to reduce the incidence of GDM [21][22][23][24] and pre-eclampsia [23,[25][26][27][28][29], two pregnancy-related complications implicated in poor neonatal outcomes and downstream child health. Systematic reviews and meta-analyses looking exclusively at PA interventions during pregnancy have shown success in restricting GWG (-0.36 kg, 95% CI: -0.64 to -0.09 kg [30]; -0.61 kg, 95% CI: -1.17, -0.06 [31]; -0.91kg , 95% CI: -1.76, -0.06 [32]) but few studies have been designed to examine the effects on longer-term child growth or body composition [33][34][35].…”
mentioning
confidence: 99%